Conhecimento e prática em saúde bucal de cuidadores de idosos institucionalizados em Vitória, Brasil - Gomes, Patrícia da Costa (2017)
Caregivers play an important role in maintaining adequate oral health of elderly people. Thus, the aim of this study was to evaluate the oral health knowledge and practice of caregivers of institutionalized elderly people in the city of Vitória, state of Espírito Santo, Brazil. The materials and methods consisted of a cross-sectional study with a sample of 27 caregivers from a long-term institution. A interview form to assess the characteristics of caregivers as profile, training, knowledge, practice and prevention related to oral health was used. For data analysis, absolute and relative frequency descriptions were performed. The results showed that the predominant profile of the caregivers was female (63%) and 81.5% were trained to work with elders. Although most of them knew the necessity of brushing the teeth at least three times a day to prevent dental caries and periodontal disease (88.9%); 44.5% said that the oral hygiene by caregivers for the elderly was performed under supervision only once a day. Regarding the hygiene of dentures, only one caregiver mentioned the use of specific chemical agent and 40.7% declared themselves unaware of any oral care protocol at the institution. 85% believed in a correlation between general health and the presence of oral diseases and 70% said not knowing about oral diseases that could affect elderly with denture in function. 59.3% answered that the type of food may influence the elderly oral health. It was concluded that caregivers do acknowledge and regognize the importance of the oral health, but the practice is not proportional to the declared knowledge.